Penggambaran Hubungan Ibu dan Anak dalam Iklan Lifebuoy Versi Akar Kuat di Bulan Suci - Nugroho, Surya Andrie; Agustrijanto (Research and Community Service UNIVERSITAS KALBIS, 2024)
The figure of a mother is very special within the family. A good relationship between a mother and her child can shape the child's behavior, character, and mentality. The strong bond between a mother and her child is portrayed in the Lifebuoy advertisement titled “Akar Kuat di Bulan Suci” ('Strong Roots in the Holy Month'). The aim of this study is to explore the depiction of the mother-child relationship in the Lifebuoy advertisement “Akar Kuat di Bulan Suci”. This research applies the Theory of Social Construction of Reality in Mass Media through three social processes: externalization, objectification, and internalization. It adopts a constructivist paradigm with a qualitative approach, utilizing Content Analysis Method with Charles S. Peirce's semiotic analysis technique of Sign, Object, Interpretant. The findings reveal that the portrayal of the mother-child relationship in the Lifebuoy advertisement 'Akar Kuat di Bulan Suci' depicts an emotional connection, characterized by gestures shown between the mother and child. These gestures by the mother towards her child signify both physical and emotional affection.